Integrating Physiotherapy into Primary Health Care Practice in Nigeria: A call to action. (2014)
In Nigeria, Physiotherapy is often regarded as a second-contact health service suitable only for secondary and tertiary health facilities that are usually located in urban centers. Yet many patients who require the professional services of a physiotherapist are unable to access it either as a result of non-availability of physiotherapy centers and or non-affordability by the populace occasioned by cost and distance to location of the health facilities. Bringing physiotherapy closer to the doorsteps of those who need it in low-income societies can be ensured through its inclusion in primary health care models. This is because Primary health centers are located with short distances in the community and are funded by the government. We discussed the relevance of primary health care physiotherapy model in promoting health of the population and the feasibility of this model in a low-income society such as Nigeria.